Optimization of Battery Power Efficiency in Baby Incubator Transport Through PID-Fuzzy Control - TOKAN, MARIA; F, Ajesh (Jurnal Teknokes, 2024)
Baby incubator transport is an essential device in supporting the stability of a baby's body temperature during medical transportation. However, one of the main challenges is the efficient use of battery power, which affects the duration of operation without recharging, especially in emergency situations. An inefficient temperature control system can accelerate power drain, thus threatening the safety of the infant during the transportation process. This research aims to analyze the use of temperature control in Baby Incubator Transport with PID-Fuzzy method to assess the efficiency of battery power usage. The main contributions of this research are Improving battery power efficiency and extending battery life thereby reducing the need for battery replacement and saving operational costs, integrating PID-Fuzzy control concepts in medical devices such as baby incubator transport. This research uses a combined PID-Fuzzy method on a baby incubator transport device. This method is done to maintain temperature stability as well as battery power consumption. The research findings show that the use of the PID-Fuzzy control method can reduce power consumption by up to 70%. In addition, temperature stability is better maintained with smaller deviations, making it safer to use during baby transportation. The system is able to respond to temperature changes more quickly and reduce overload on the power system. For further research, it is recommended to replace the battery with a Lipo Lithium-polymer battery, Heater is adjusted to the power consumption and wattage is lowered, Blower Chamber size is replaced with a larger one. In addition, further testing is needed to test the durability of the system in environments with more extreme conditions and longer transportation simulations.